Tuna Fish As A Source Of Inspiration For Ideas In The Creation Of Paintings - Gangga, I Putu Bisma Maha; Adnyana, I Wayan; Utami, Ni Made Purnami (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
The final report of this independent study/project raises the theme "Tuna Fish as a Source of Inspiration in the Creation of Paintings". The phenomenon of fish bombing, especially referring to tuna which still often occurs even though it has been urged and given a deterrent effect by giving fines or imprisonment, but there are still many who use explosives or bombs to hunt fish, the cause of fishing perpetrators is mostly aimed at getting a lot of profit in a short time and with the energy expended is so limited. The problem faced is how to apply the concept and how to visualize the meaning contained in the painting, the purpose to be achieved in the creation of this work is to appeal to the wider community, especially those in coastal areas and to ISI Denpasar students not to use explosives or bombs in catching tuna and other fish. Through the idea of creativity and imagination channeled into the form of paintings by combining certain techniques, styles, symbols, colors, and references to achieve the desired goals and meanings. It can be concluded that tuna fish inspire writers in creating paintings and develop imaginative ideas and ideas that will become valuable and meaningful works. With the creation of this work, it is hoped that it will be able to convey messages and meanings, as well as an educational medium from the impact of tuna bombing.